(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
This paper works on the construction of national sociability in the dramatic introductions to “El triunfo de la libertad” and “Tragedia de Guillermo Tell” by the patriot and thinker Bernardo Vera y Pintado. To do this, the texts are analyzed based on the representation of the indigenous people as part of the construction of a new society that includes them in the social relations of Chileans and, on the other hand, in the construction of O’Higgins as a hero and figure of national independence. The proposal understands that the works represent the view regarding a new form of relationship between citizens in a recently liberated town and a political project of the nation that points to a homogenizing utopian horizon.